Game Online dan Perkembangan Moral Perspektif Jean Piaget: Studi Kasus Mahasiswa Angkatan 2021 - Muhamad Hilman Firmansyah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the effect of online games on the moral development of Jean Piaget's perspective. This research uses a qualitative approach through literature and field studies using observational techniques. The formal object in this research is Jean Piaget's cognitive theory, while the material object of this research is the influence of online games on moral development. The context of this research is students of class 2021. This research begins by describing online games that are popular among university students and finding out their influence on moral development using Jean Piaget's perspective. The results of the discussion show that online games have an influence on their users. This study concludes that playing online games by borrowing Jean Piaget's theory of moral development has positive and negative influences. So this research recommends educational institutions to look at the wider influence of online game users among Indonesia's younger generation.